The NLRP3 inflammasome: role in airway inflammation. Issue 2 (22nd January 2014) - Im, H.; Ammit, A. J.
Summary Asthma is characterized by airway inflammation, airway hyperresponsiveness and airway remodelling. Uncontrolled airway inflammation or repeated asthma exacerbations can lead to airway remodelling, which cannot be reversed by current pharmacological treatment, and consequently lead to decline in lung function. Thus, it is critical to understand airway inflammation in asthma and infectious exacerbation. The inflammasome has emerged as playing a key role in innate immunity and inflammation. Upon ligand sensing, inflammasome components assemble and self‐oligomerize, leading to caspase‐1 activation and maturation of pro‐IL‐1β and pro‐IL‐18 into bioactive cytokines. These bioactive cytokines then play a pivotal role in the initiation and amplification of inflammatory processes. In addition to facilitating the proteolytic activation of IL‐1β and IL‐18, inflammasomes also participate in cell death through caspase‐1‐mediated pyroptosis. In this review, we describe the structure and function of the inflammasome and provide an overview of our current understanding of role of the inflammasome in airway inflammation. We focus on nucleotide‐binding domain and leucine‐rich repeat protein 3 (NLRP3) inflammasome as it is the best‐characterized subtype shown expressed in airway and considered to play a key role in chronic airway diseases such as asthma.